Keefektifan Organisasi Perguruan Tinggi (Studi Kasus Pada Universitas Muhammadiyah Palangkaraya) - Sonedi Sonedi (Anterior Jurnal, 2013)
This research aims at describing the effectifity of Universty of Muhammadiyah Palangkaraya organization that is seen from the efficiency and productivity sides and describing the ability of adaptation and development of University of Muhammadiyah Palangkaraya organization. The findings of research result showed that: 1) to reach the effectifity and productivity were done the steps: reaching of the formulation of purpose, the determination the field or unit as the section that will do the purpose attainment, deciding the phase of time that was needed, deciding the instrument that could be used to reach the purpose. By the steps University of Muhammdiyah Palangkaraya could produce the out put approriate the target given both quantitaitive and qualitative. 2) The ability of adaptation and development of University of Muhammadiyah Palangkaraya, they were seen from the efforts from the leader in overcoming the problem or challenge both internal and external, so this university still keep exist and developing accord with society expectation, although the donation factor became the key of university development. Based on the data accord with the research focus, so it could be concluded that the organization of college of Muhammadiyah Palangkaraya was effective.